The Effect of Teacher Motivation and Teacher Work Discipline on the Nomination of Private School Principals in Karanganyar Indonesia - Sutarman, Sutarman; J.A, Sutarno; Suryani, Nunuk; Asrowi, Asrowi (Universitas Islam Negeri Raden Intan Lampung, 2021)
This research aimed to determine teachers' motivation and work discipline towards the nomination of primary schools principal in the Karanganyar Regency. This research employed a quantitative method with a cross-sectional design. The research population was elementary school teachers in Karanganyar Regency. The research sample was 40 teachers determined through a random sampling technique. The researchers collected the data using questionnaires to be analyzed using multiple logistic regression analysis techniques. The results showed that motivation significantly influenced (p = 0.027) the nomination of the principal with an Odds Ratio of 14.19 (OR = 14.19; 95% CI = 1.36–148.27). Furthermore, work discipline significantly affected (p = 0.037) the nomination of the principal with an Odds Ratio of 8.38 (OR = 8.38; 95% CI = 1.14- 61.91). Therefore, the researchers concluded that (1) teacher motivation posed positive and significant effects on the nomination of the primary school principal in Karanganyar Regency and (2) teachers’ work discipline posed positive and significant effects on the nomination of the primary school principal in Karanganyar Regency. This research is expected to motivate teachers to have high achievements to be promoted and prepare themselves to collect the requirements for principal nomination.